Modeling of multi lane highway traffic and analysis of jam formation - İmrem, Ayşe Nihan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Have you ever wondered how many hours you have spent sitting in a bumper-to-bumper traffic? We wrote a simulation code for defining both the Turk- ish driver behavior and their effect to traffic flow. We propose a Cellular automata (CA) model for traffic flow from the European side to Asian side over the Bosphorus on the Fatih Sultan Mehmet Bridge with the aim of acquiring physically significant and realistic data for a simple virtual highway consisting of four lanes, an on-ramp, an off-ramp, and an auxiliary lane. We arrange the Nagel-Schrenkenberg single lane model as multi-lane and we add different local rules to show various traffic behavior. Traffic research still cannot fully predict under which conditions a traffic jam may suddenly occur. The aim of this thesis is to define what causes such traffic jams from a physicist’s point of view. The possible reasons for the jam formation can be the frequent lane changing, less headway and high density. These parameters are changed and analyzed for their effect on the traffic flow. We have studied space-time diagrams showing the position of all vehicles in each time step, and ”fundamental diagrams” showing the relationship between flow and density. To test the psychological aspects of the driver behavior and cultural side of the traffic flow problem, a foreign graduate student and a local graduate student approach this problem using different parameters related to our traffic cultures for the same road portion.
Keywords: Cellular automata.; Traffic flow -- Mathematical models.